2021
DOI: 10.1186/s40168-021-01081-2
|View full text |Cite|
|
Sign up to set email alerts
|

A probiotic has differential effects on allergic airway inflammation in A/J and C57BL/6 mice and is correlated with the gut microbiome

Abstract: The phenotypes of allergic airway diseases are influenced by the interplay between host genetics and the gut microbiota, which may be modulated by probiotics. We investigated the probiotic effects on allergic inflammation in A/J and C57BL/6 mice. C57BL/6 mice had increased gut microbiota diversity compared to A/J mice at baseline. Acetate producer probiotics differentially modulated and altered the genus abundance of specific bacteria, such as Akkermansia and Allistipes, in mouse strains. We induced airway inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 78 publications
0
11
0
1
Order By: Relevance
“…V-Lep ob /J, and NOD) is similar to each other on the bacterial relative distribution on higher taxonomic levels [ 66 ], while another study indicated mouse strain had remarkable effect on the abundance of Akkermansia and Lactobacillus [ 65 ]. Also, a recent study has shown that a probiotic played differential roles on allergic airway inflammation in A/J and C57BL/6 mice and was associated with gut microbiome [ 67 ]. Although gut microbiota is stable, it varies both in time and in different strains.…”
Section: Discussionmentioning
confidence: 99%
“…V-Lep ob /J, and NOD) is similar to each other on the bacterial relative distribution on higher taxonomic levels [ 66 ], while another study indicated mouse strain had remarkable effect on the abundance of Akkermansia and Lactobacillus [ 65 ]. Also, a recent study has shown that a probiotic played differential roles on allergic airway inflammation in A/J and C57BL/6 mice and was associated with gut microbiome [ 67 ]. Although gut microbiota is stable, it varies both in time and in different strains.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that 95% of diseases are related to gut microbiota. In addition to gastrointestinal diseases, metabolic diseases, gut microbiota is also related to various system diseases, such as nervous system ( Vicentini et al., 2021 ; Saldana-Morales et al., 2021 ), respiratory system ( Zheng et al., 2020 ; Casaro et al., 2021 ), cardiovascular system ( Khan et al., 2021 ; Deng et al., 2022 ), tumor ( Yang et al., 2020 ; Chung et al., 2021 ; Murphy et al., 2021 ), etc. disease related.…”
Section: Gut Microbiomementioning
confidence: 99%
“…Asthma is an airway chronic inflammatory disorder characterized as a heterogeneous disease. In this review, we focused on the allergic asthma, which is the most common type of this disease ( 110 ). Allergic asthma is also associated with sensitization to aeroallergens such as air pollution, bacteria, pollen and virus.…”
Section: Effects Of Butyrate In Distinct Respiratory Diseasementioning
confidence: 99%
“…It is well-established in the literature that perturbations in the gut microbiota are linked to allergic asthma ( 14 , 111 ). For instance, the use of antibiotics during pregnancy was found to be associated, in a dose-dependent way, with the severity of asthma in the offspring ( 108 ), and several studies have shown beneficial effects of soluble fiber intake and SCFA-producing probiotics for asthma inflammation throughout different stages of life ( 109 , 110 ). In this sense, SCFAs may influence the development of asthma via epigenetic regulation of distinct immune cell populations ( 19 ).…”
Section: Effects Of Butyrate In Distinct Respiratory Diseasementioning
confidence: 99%